Computer Science Is Not a Science. - Abrahams, Paul W.; Lee, Graham; Hayes-Roth, Rick; Stabile, Larry; Hewitt, Carl; Gupta, Basudeb (Communications of the ACM, 2013)
Letters to the editor are presented in response to articles from previous issues, including "Where Is the Science in Computer Science?" by Vinton G. Cerf in the October 2012 issue, "The Foresight Saga, Redux," by Peter G. Neumann from the October 2012 issue on information technology and computer security, and "Software Needs Seatbelts and Airbags," from the September 2012 issue by Emery D. Berger on the techniques of computer software programming.